Construction Validity Test of The Indonesian Muslims Personality Inventory Measurement Instrument on Generation Z Students - Deslinda, Gadis; Hapsari, Maharani Tyas Budi; Muhadiyatiningsih, Siti Nurlaili; Badriyah, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to develop an Islamic personality assessment tool for Muslim university students in Indonesia based on Al-Ghazali's theory. This study was conducted on 584 samples consisting of 491 women and 93 men. The sampling technique used in this study was purposive sampling. Although Islamic personality assessment tools already exist in Indonesia, current instruments lack diverse data analysis methods and detailed confirmatory factor analysis. The novelty of this research on the Indonesian Muslim Personality Inventory lies in its use of more varied data analysis and reliability estimation employing both EFA and CFA approaches. This measurement tool consists of 26 valid items with 5 factors that show an increase in the feasibility of the good model. Initially, the Indonesian Muslim Personality Inventory consisted of 41 items, but 15 items were gradually eliminated because they did not meet psychometric criteria. This instrument comprises 26 final items, with an RMSEA of 0.067, SRMR of 0.075, CFI of 0.970, TLI of 0.965, and GFI of 0.972. Theoretically, this research enriches the literature on psychological measurement while supporting the development of further research and interventions in the field of Islamic psychology. Keywords: Muslims Personality, Measuring Instrument, Z Generation Student